The Closed Discussion of English Learning Group with Writing Based in Facebook - Moh. Hafidz; Riryn Fatmawaty (STKIP PGRI Lubuklinggau, 2022)
This study investigated the participants’ performance in the closed discussion of English learning group. This research purpose is to know the distinction between the official and un-official discussion of English learning in writing based. The taking notices is the instrument of this research that adopted from the recommended previous articles. The results, the most participants really respect on the daily topics and grammar. The daily topic is displaied in humorous caption that can activate participants to give some different comments. Absolutely, it can enrich the participants’ vocabularies. The grammatical skill is also performed in posting and commenting technique, it enables participants to personally practice their grammar knowledge, and this technique encourages the participants’ self-confident to write a sentence in the correct tenses.